Characterization of Ultrasound-Extracted Pouteria splendens Fruit Extracts: Phytochemical Profiling and Evaluation of Antioxidant and Cytotoxic Effects - Alejandro Madrid; Valeska Calderón; Valentina Silva; Patricio Novoa; Carlos Jara; Alejandra Catalina Möller; Joan Villena; Cristóbal Balada; Leda Guzmán; Iván Montenegro (Foods)
This study investigated the bioactive potential of Pouteria splendens fruit through ultrasound-assisted extraction, analyzing peel and pulp. The pulp exhibited a higher phytochemical content, with 179.67 mg GAE/g d.w. and 208.48 mg QE/g d.w., approximately 1.5 times more than in the peel. Fifty phenolic compounds were identified by HPLC-MS, including four types of phenolic acids, with hydroxybenzoic (52%) and hydroxycinnamic (42%) as the two predominant ones, and six types of flavonoids, with flavonols (26.67%) and flavones (23.33%) as the two most prevalent. The pulp demonstrated greater antioxidant activity than the peel and the commercial controls (BHA and BHT) in the DPPH assay (IC50 2.54 mg/mL); however, it showed lower activity in the FRAP assay. Cytotoxic activity was evaluated in cancerous (MCF-7, HT-29, and PC-3) and non-cancerous (CCD 841 CoN and HEK-293) cell lines. Notably, the pulp exhibited remarkable cytotoxic activity against colon cancer cells (HT-29), with an IC50 of 50 µg/mL, and possible selectivity by not showing significant activity in non-cancerous cells (CoN and HEK). These results suggest that P. splendens, and particularly its pulp, is a valuable source of bioactive polyphenols, with potential for the food and pharmaceutical industries.